2000
DOI: 10.1046/j.1525-1446.2000.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

A Student‐Directed Community Project to Support Sexually Abused Women Veterans Suffering from Post‐Traumatic Stress Disorder

Abstract: While awareness of post-traumatic stress disorder (PTSD) and sexual abuse continues to grow, it has only been during the past few years that the military has realized the prevalence and impact of sexual abuse inflicted upon women while on active military duty. Though Veteran Administration (VA) agencies throughout the United States have given concerted attention to this problem, published resources specific to PTSD and military sexual abuse have been limited. In this article the authors present the results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Meeting with other women in a safe environment can help to challenge the critical self-talk that the women in our study sometimes engaged in, and the belief that one is alone in her experiences. In one study conducted of women veterans who experienced sexual trauma, women reported that at certain stages of their recovery, they would have found it helpful to know that others had similar experiences (Wing & Oertle, 1998 as cited in Wing et al, 2000). A support group can provide women with the opportunity to offer support to each other; this potential for altruism can be very beneficial therapeutically (Yalom, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Meeting with other women in a safe environment can help to challenge the critical self-talk that the women in our study sometimes engaged in, and the belief that one is alone in her experiences. In one study conducted of women veterans who experienced sexual trauma, women reported that at certain stages of their recovery, they would have found it helpful to know that others had similar experiences (Wing & Oertle, 1998 as cited in Wing et al, 2000). A support group can provide women with the opportunity to offer support to each other; this potential for altruism can be very beneficial therapeutically (Yalom, 1995).…”
Section: Discussionmentioning
confidence: 99%